The Boma: How - and why - do we talk about science? - International Livestock Research Institute (International Livestock Research Institute, 2022)
If you're not a researcher, why should you care about science? Why does science communication matter to research? In the second of a two-parter featuring ILRI Emeritus Fellow Susan MacMillan, Brenda Coromina and Elliot Carleton question what the difference is between science communication, and science advocacy, finding out how the International Livestock Research Institute's (ILRI) communications have changed over the years, and why. "We're not science for science's sake," says Susan of ILRI. "We have a mission. We have to go further than just the science." They discuss how social media can be a positive force for science, and what science writing has in common with storytelling. It's not enough to simply put the information out in easy-to-understand terms. Science communication is a big responsibility, and can have a tremendous impact on the world. So whose voice should be heard - and who should be doing the storytelling?